Desregulamentação e mudança institucional no mercado de café: um estudo de caso na região das matas de Minas - Marisa Alice Singulano Alves (2015)
This study addresses the institutional changes resulting from the deregulation of the coffee market, which started in the 1990s, as well as its consequences in terms of market restructuring and how the producers in the Matas de Minas region have adapted to the new context. The extinction of the IBC left a gap in the coffee market coordination, which was gradually filled by other social actors, both from public bureaucracy and private organizations. Regarding coffee policy, there was a depletion of many actions at first. Then, there was a process of decentralization of this policy and a greater openness in decision-making, with an increase in the participation of sectorial organizations. The changes in the institutional environment have set incentives for the creation of producer organizations in several regions, including in the studied area. The Matas de Minas region has undergone major changes since the 1990s, which are expressed in two basic dimensions: a change in reputation - from a region known for its low quality coffee to an increasing recognition for producing good quality coffee; and a process of adaptation of the producers to the new institutional and economic conditions, through the differentiation of coffee qualities. In the analysis of these processes, we have relied on the institutionalist theory, giving emphasis to the social and political construction of market structures and to the relationship between public bureaucracies and social organizations in the context of liberalization. We also highlight the 'social construction of quality' as a key category for the analysis of the strategies of producers in this context and of the new local market configuration. The results of our research indicate that the changes in the institutional environment have influenced the production and marketing conditions, creating incentives and constraints to the formation of economic strategies of producers - which relate to specific forms of coordination of coffee transactions.